Role Ambiguity and Role Overload as Important Predictors of Work-Family Conflict - NurIzzaty Mohamad; Azman Ismail; Nurul Muna Mohamad; Sholihien Ahmad; Zulkefli Yahy (Humaniora, 2016)
Work stress hadtwo important components: role ambiguity and role overload. This research used a cross-sectional research design because it permited the researchers to integrate the work stress literature and the actual survey as the main procedure of collecting data for this study. Therefore, this study was conducted to determine the relationship between the work stress and work-family conflict of workers using 97 questionnaires collected from navy in Malaysia. The outcomes of testing hypothesis by using smartPLS path model confirmed two important findings. First, role ambiguity was significantly correlated with work-family conflict. Second, role overload was significantly correlated with work-family conflict. This result confirms that the ability of employees to appropriately manage the ambiguity and overload in performing daily job may reduce reduce work-family conflict in the studied organization.